STUDY OF CERIA STABILIZED ZIRCONIA MICROSPHERES MORPHOLOGY BY SMALL-ANGLE SCATTERING AND MICROSCOPY - Andon Insani; Arum Patriati; Nadi Suparno; Ratih Langenati; Siriwat Soontaranoon; Ridwan Ridwan (Jurnal Sains Materi Indonesia, 2019)
STUDY OF CERIA STABILIZED ZIRCONIA MICROSPHERES MORPHOLOGY BY SMALL-ANGLE SCATTERING AND MICROSCOPY. Ceria stabilized zirconia microspheres of about 500 microns were prepared by external gelation. The morphology in nano and micro scale of the microsphere was evaluated. The nanostructure of CSZ microsphere after drying was studied by small angle neutron and x-ray scattering (SANS and SAXS). In this state, the existing of the mixture of ceria oxide and zirconia oxide was observed inside the polymer matrix. The roundness and surface properties of the CSZ microsphere were observed under the optical microscopy (OM) and scanning electron microscopy (SEM). The data showed their good size uniformity, smooth surface, but also the imperfect phase of the gelation.